The use of diagnoses in mental health service eligibility and exclusion criteria. (2nd January 2021) - Allsopp, Kate; Kinderman, Peter
Abstract: Background: Diagnoses are controversial but ubiquitous in mental health; however, whether they are essential features of service entry has not been analysed. Aim: To investigate the use of diagnosis in the service entry criteria of UK NHS adult mental health services. Methods: Freedom of Information requests were made to 17 NHS adult mental health Trusts; responses were analysed thematically. Results: Four service types were identified: broadly diagnostic, problem-specific, supporting specific life circumstances and needs-led. Diagnoses were used frequently but not universally. Non-diagnostic factors were central to service entry criteria. Conclusions: Diagnoses were neither necessary nor sufficient in-service entry criteria. Broad clusters of difficulties were used rather than specific diagnoses. Extensive exceptions revealed diagnoses as inefficient proxies for risk, severity and need. Differences across criteria appeared largely driven by professional competencies. Implications for innovative care pathways include preventative services and working with psychosocial factors.